Prediksi Curah Hujan Menggunakan Fuzzy Time Series - Adhi Susano; Wulan Anggraeni (Neolectura, 2021)
Flood is one of the problems faced by DKI Jakarta Province. To be able to reduce losses caused by flooding is to predict rainfall. The type of research is quantitative research using rainfall prediction method using Fuzzy Time Series (FTS) which was developed by Stevenson & Porter (2009). The data used is rainfall data at Kemayoran Station in the period January 2018 to December 2020. The prediction accuracy results state that the FTS method has poor accuracy so that improvements are needed in the formation of interval intervals.